Spectrophotometric Determination of Creatinine Using a Modified Diazo Coupling Reaction: A Reliable Approach for Biomarker Analysis in Human Serum - Duaa Abdulzahraa Al-Rammahi (American Journal of Biology and Natural Sciences, 2026)
This study introduces a novel and modified spectrophotometric method for the precise quantitative determination of creatinine in human serum samples, addressing the need for more specific and reliable renal function biomarkers. The proposed approach is centered on a Diazo coupling reaction, which is inherently characterized by high selectivity, sensitivity, and the formation of a stable, dark-colored product that is easily detectable. This method was developed to overcome the well-documented specificity limitations of the traditional Jaffe reaction, which is often susceptible to interference from other chromogens in serum. A key innovation of this work is the introduction of Thymole as a highly effective coupling agent, which, under optimized reaction conditions, significantly enhances the specificity towards creatinine. A systematic optimization of critical reaction parameters, including acid concentration, the choice of base, reaction time, and temperature, was performed to achieve maximum absorbance of the resultant yellow azo product at a wavelength of 403 nm. The developed method demonstrates excellent analytical performance, adhering to Beer–Lambert’s law within a clinically relevant concentration range of 1.2–8.0 mg/dL, with a high coefficient of determination (R² = 0.9982). Furthermore, the low limit of detection (LOD = 0.39 mg/dL) underscores the method's superior sensitivity. Its efficacy was successfully validated through application to real human serum samples, showing a strong correlation with results obtained from the hospital-based Jaffe method. In conclusion, this simple, rapid, sensitive, and cost-effective technique offers a reliable and robust alternative for clinical and diagnostic applications, promising improved accuracy in creatinine measurement.